Studi Penyimpanan Entres Wani Ngumpen Bali (Mangifera caesia Jack var. Ngumpen Bali) terhadap Keberhasilan Grafting - ANAK AGUNG NGURAH DHARMA SEPUTRA; IDA AYU PUTRI DARMAWATI; A.A. MADE ASTININGSIH (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2022)
Study on Entres Storage of Wani Ngumpen Bali (Mangifera caesia Jack var. Ngumpen Bali) On Success of Grafting Wani Ngumpen Bali (Mangifera caesia Jack var. Ngumpen Bali) is one of tropical fruit which belongs to genius mangifera. The obstacle that are often faced in propagation of Wani Ngumpen Bali by grafting are the long distance between the mother plant and the nursery location, so it takes time to be grafted. The purpose of this research is to study the scion storage of Wani Ngumpen Bali on success of grafting. The research start from February to April 2021, located in Sudaji Village, Sawan District, Buleleng Regency, Bali. The experimental design used was a randomized block design with a single factor. The factor studied was the length of storage of scion which consisted of 7 levels, namely scion were not stored, scion were stored for 1, 2, 3, 4, 5 and 6 days. The treatment was repeated 4 times with each treatment using 2 plants, so there were 56 experimental units. Parameter observed were the percentage of grafting successfulness, shoot length, and number of leaves formed. The results showed that the grafts that were directly connected had the highest percentage of live connections of 62.5%, followed by those that were stored for one day had a percentage of 50.0% then those that had a two-day shelf life had a percentage of 37.5%. Entres with a shelf life of three to six days failed to grow with a percentage of 0%.